E- Service Quality, Ease of Use, Usability and Enjoyment as Antecedents of E-CRM Performance: An Empirical Investigation in Jordan Mobile Phone Services - Al-Momani, Khalid; Mohd. Noor, Nor Azila (School of Business and Management Institut Teknologi Bandung, 2009)
Electronic Customer relationship management performance E-CRM is a comprehensive business and marketing strategy that integrates people, process, technology and all business activities for attracting and retaining customers over the internet and mobile phone to reduce costs and increase profitability by consolidation the principles of customer loyalty. Therefore, the results of E-CRM performance are repeat purchase, word of mouth, retention, cross buying, brand loyalty and customer satisfaction. The keen competitive in the communication and mobile phone service market place and the increasing numbers of mobile phone users all over the world has influence the researchers to investigate ease of use, usability, enjoyment and e- service quality as antecedents of electronic customer relationship management performance in mobile phone services industry. 488 questionnaires have returned and analyzed. Four factors been tested to investigate the relationship with E-CRM performance. The analysis shown that e- service quality, ease of use and usability was positively significant towards E-CRM performance. Enjoyment has failed to predict E-CRM performance. This paper makes a theoretical and methodological contribution and suggestion for the managers in improving their E-CRM performance in mobile phone service industry. Key words: E-customer relationship management performance, Mobile Phone Services, e- service quality, ease of use, enjoyment and usability.Key words: relationship management, CRM